Efficient SMN Rescue following Subcutaneous Tricyclo-DNA Antisense Oligonucleotide Treatment - Valérie Robin; Graziella Griffith; John-Paul L. Carter; Christian J. Leumann; Luis Garcia; Aurélie Goyenvalle (Elsevier, 2017)
Spinal muscular atrophy (SMA) is a recessive disease caused by mutations in the SMN1 gene, which encodes the protein survival motor neuron (SMN), whose absence dramatically affects the survival of motor neurons. In humans, the severity of the disease is lessened by the presence of a gene copy, SMN2. SMN2 differs from SMN1 by a C-to-T transition in exon 7, which modifies pre-mRNA splicing and prevents successful SMN synthesis. Splice-switching approaches using antisense oligonucleotides (AONs) have already been shown to correct this SMN2 gene transition, providing a therapeutic avenue for SMA. However, AON administration to the CNS presents additional hurdles. In this study, we show that systemic delivery of tricyclo-DNA (tcDNA) AONs in a type III SMA mouse augments retention of exon 7 in SMN2 mRNA both in peripheral organs and the CNS. Mild type III SMA mice were selected as opposed to the severe type I model in order to test tcDNA efficacy and their ability to enter the CNS after maturation of the blood brain barrier (BBB). Furthermore, subcutaneous treatment significantly improved the necrosis phenotype and respiratory function. In summary, our data support that tcDNA oligomers effectively cross the blood-brain barrier and offer a promising systemic alternative for treating SMA.